Book Review: Structures of Indifference: An Indigenous Life and Death in a Canadian City - Stelkia, Krista (International Indigenous Policy Journal, 2020)
The case of Brian Sinclair, a First Nations man who died in a Winnipeg, Manitoba, hospital emergency room in 2008 after waiting 34 hours for medical care to treat a preventable infection, represents the degree to which structural indifference exists within Canadian society. This article reviews the book Structures of Indifference: An Indigenous Life and Death in a Canadian City by Mary Jane Logan McCallum and Adele Perry, published by University of Manitoba Press in 2018. The review will provide a content summary of each chapter along with an assessment of the strengths and weaknesses of the book. A critical analysis of how the authors examined this case, using a place-based approach of the city, the hospital, and life and death of Brian Sinclair, is discussed. The review will identify critical concepts and lessons relevant to the development of Indigenous health policy and practice, which will be applicable to both a national and international audience.